Control of Aptamer Function Using Radiofrequency Magnetic Field. (11th July 2011) - Taira, Kenichi; Abe, Koichi; Ishibasi, Takayuki; Sato, Katsuaki; Ikebukuro, Kazunori
Abstract : Remote control of aptamer function has allowed us to control protein function in space and time. Here, we propose a novel control system for aptamer function by radiofrequency magnetic field- (RFMF-) induced local heating of a gold nanoparticle conjugated with an aptamer. In this study, we used a 31-mer thrombin-binding aptamer (TBA), which can inhibit thrombin activity, as a model aptamer. We evaluated the RFMF control of the inhibitory activity of a gold nanoparticle-conjugated TBA. To evaluate the effect of RFMF on enzymatic activity, we utilized a complementary DNA strand that maintains the broken structure during the activity assay. We observed a decrease in the inhibitory activity of TBA after RFMF irradiation. It indicates that RFMF is capable of controlling the TBA structure. Because RFMF allows noninvasive control of aptamer function, this strategy is expected to be novel way of controlling aptamer drug activity.